Factors influencing the behavioural intention to use the internet as teaching-learning tool in home economics. - Phua, Peng Lin; Wong, Su Luan; Abu, Rosini (2011)

(untitled)
The extended Technology Acceptance Model (TAM) is employed to explore how the behavioural intention (BI) of Home Economics (HE) teachers to use the Internet as a teaching tool is influenced by four factors, viz. Internet attitude (IA), perceived usefulness (PU), perceived ease of use (PEU) and perceived enjoyment (PE). The findings suggest that HE teachers’ BI to use the Internet is positively correlated (n = 106, p < 0.0005) with IA (r = .67), PU (r = .63), PEU (r = .54) and PE (r = .70). The implications on the teaching-learning of HE based on the findings of this study are discussed.